Use of neem (Azadirachta indica A. Juss) as a biopesticide in agriculture: A review - bhandari, sudip; Adhikari, Kripa; Niraula, Dikshya; Shrestha, Jiban (Future Science, 2020)
Neem (Azadirachta indica A. Juss) is a member of Meliaceae family, a fast-growing tropical evergreen plant whose products were found effective against economically important insect pests and diseases. All parts of this plant particularly leaf, bark, and root extracts have the biopesticidal activities. Azadirachtin, a biopesticide obtained from neem extract, can be used for con-trolling various insect pests in agriculture. It acts on insects by repelling them, by inhibiting feeding, and by disrupting their growth, and reproduction. Neem-based formulations do not usually kill insects directly, but they can alter their behavior in significant ways to reduce pest damage to crops and reduce their reproductive potential. The neem is considered as an eas-ily accessible, eco-friendly, biodegradable, cheap, and non-toxic biopesticide which control the target pests. Thus, this re-view highlighted the extract, byproducts and roles of neem that can be used as potential biopesticide in agriculture.